Analysis of a Novel Mechanically Adjusted Variable Flux Permanent Magnet Homopolar Inductor Machine with Rotating Magnetic Poles for Flywheel Energy Storage System - Qing Li; Mingcheng Lyu; Jiangtao Yang; Shoudao Huang (CES Transactions on Electrical Machines and Systems, 2022)
Permanent magnet homopolar inductor machine (PMHIM) has attracted much attention in the field of flywheel energy storage system (FESS) due to its merits of simple structure, brushless excitation, and rotor flywheel integration. However, the air-gap flux generated by the PM cannot be adjusted, which would cause large electromagnetic losses in the standby operation state of FESS. To solve this problem, a novel mechanically adjusted variable flux permanent magnet homopolar inductor machine with rotating magnetic poles (RMP-PMHIM) is proposed in this paper. The permanent magnet poles are rotated by an auxiliary rotating device and the purpose of changing the air-gap flux is achieved. First, the structure and operation principle of the proposed RMP-PMHIM are explained. Second, the flux weakening principle of the RMP-PMHIM is analyzed and the equivalent magnetic circuit models under different flux weakening states are built. Third, the parameters of the PM and its fixed structure are optimized to obtain the good electromagnetic performance. Fourth, the electromagnetic performance, including the air-gap flux density, back-EMF, flux weakening ability, loss, etc. of the proposed RMP-PMHIM are investigated and compared. Compared with the non-rotating state of the PM of RPM-PMHIM, the air-gap flux density amplitude can be weakened by 99.95% when the PM rotation angle is 90 degrees, and the no-load core loss can be suppressed by 99.98%, which shows that the proposed RPM-PMHIM is a good candidate for the application of FESS.